2016
DOI: 10.1080/00202967.2016.1162400
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the finishing characteristics in an internal tube finishing process by magnetic abrasive finishing combined with electrolysis

Abstract: In this research, the finishing characteristics in a tube's internal finishing process using the method of magnetic abrasive finishing (MAF) combined with electrolysis has been studied. Electrolysis produces an aluminium oxide film that accelerates the removal of the initial hairline morphology on the surface. Subsequently, the film is removed with MAF. This process significantly minimises the surface roughness in a reduced time. The way the finishing conditions, such as the polepipe gap, iron particle size an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Yamaguchi et al suggested using a multiple pole-tip system with a high speed (up to 30,000 min −1 ); the experimental results proved that finishing efficiency can be improved by this method [15,16]. Furthermore, Muhamad et al developed a compound polishing method of the EMAF process from the perspective of changing the finishing characteristics of workpiece materials; the experimental results showed that both the quality of the internal surface and the finishing efficiency can be improved, and the finishing efficiency can be improved by more than 80% [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Yamaguchi et al suggested using a multiple pole-tip system with a high speed (up to 30,000 min −1 ); the experimental results proved that finishing efficiency can be improved by this method [15,16]. Furthermore, Muhamad et al developed a compound polishing method of the EMAF process from the perspective of changing the finishing characteristics of workpiece materials; the experimental results showed that both the quality of the internal surface and the finishing efficiency can be improved, and the finishing efficiency can be improved by more than 80% [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…One significant advantage in comparison to the similar techniques such as electro-polishing, the MAF process doesn't produce chemical emissions. 22 However, the magnetorheological finishing process is more robust as compared to the magnetic abrasive finishing process. This is because the carrier fluid makes the active abrasive brush much more flexible, increasing its finishing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…20 Also, the dry magnetic abrasive powder used in the MAF process results in micro-scratch, burning of grains of surface due to high heat accumulation over it, many more surface defects. 22 Therefore, in this work, magnetorheological rotary rectangular finishing method 29 has been employed to finish the external surface of the aluminium alloy cylindrical roller. To evenly distribute the colours and ingot material, the aluminium cylindrical roller requires fine and uniform finishing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations